i2F Framework to Evaluate the Effectiveness of Field-Level e-Communication - Rahnamayiezekavat, Payam; Bernold, L. (2013)
The full-scale implementation of ICT in construction offers many of opportunities such as enhanced quality and reduction in wasted resources while drastically improving the collaboration between project participants. This paper introduces a novel ICT-based information network for the construction site designed to facilitate dynamic transactions among information “suppliers” and users at their point of activity. This proposed network is used to assess the potential impact of e-communication on the outcome of construction. This evaluation is based on i2F framework unifying the procedure of evaluating the effectiveness of a piece of information considering its context. It combines information quality (InQ) and information value (InV) to calculate impact of a piece of information. Results of the performed analysis are summarized in a look-up table which models the importance of an information fragment for a process in different contexts.